Westminster Abbey
The development of fan vaulting reaches is peak in the roof of the chantry chapel of Henry Tudor at Westminster. The chantry chapel movement also may be said to reach a peak . Henry VII , the first of the Tudors, obtained the throne by conquest, and his son, Henry VIII, was later to complete the break with Rome, dissolve the monasteries and assume the title of head of the church of England.